Non-graphitizable carbon, mixed carbon powder, negative electrode for lithium ion secondary battery, lithium ion secondary battery
Through the Williamson-Hall analysis and Twolder analysis combined with process processing, difficult graphitized carbon with a specific range of strain and crystal plane spacing was prepared, and used for the negative electrode of lithium-ion secondary batteries, solving the insufficient discharge capacity in the prior art Problem, a lithium-ion secondary battery with high discharge capacity and excellent cycle characteristics has been achieved.
Patent Information
- Application Number
- CN202380013943.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-29
- Filing Date
- 2023-06-26
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2043-06-26
AI Technical Summary
The existing carbon material microcrystal diameter control method has failed to effectively obtain sufficient discharge capacity of lithium-ion secondary batteries, and the structural characteristics of difficult graphitization of carbon have not been fully utilized, resulting in insufficient charge and discharge capacity and cycle characteristics.
The strain and crystal plane spacing of carbon materials were analyzed by Williamson-Hall method, and the strain was controlled within the range of 0.081-0.120 and the crystal plane spacing was in the range of 0.360-0.370nm. Combined with Twolder analysis, crosslinking treatment, non-melting treatment, and crushing treatment. In other processes, difficult graphitization carbon with high discharge capacity was prepared and mixed with graphite to form mixed carbon powder, which was used for the negative electrode of lithium-ion secondary battery.
The high discharge capacity and excellent cycle characteristics of lithium-ion secondary batteries are achieved, and the charging and discharging performance and life of the battery are improved.
Smart Images

Figure GDA0005143228230000171 
Figure GDA0005143228230000201 
Figure HDA0004781921070000011
Abstract
Description
Technical Field
[0001] The present invention relates to hardly graphitizable carbon, mixed carbon powder, negative electrode for lithium ion secondary battery, and lithium ion secondary battery. Background Art
[0002] In recent years, due to the increasing global awareness of the need to protect the earth's atmosphere, there is a demand to reduce the use of fossil fuels and reduce CO2 emissions. As one of the solutions, power generation using renewable energy has gradually become popular. On the other hand, power generation using renewable energy, represented by solar power generation and wind power generation, is prone to output fluctuations due to time periods, meteorological conditions, and seasons. Therefore, by combining an energy storage system (hereinafter also referred to as ESS) for stabilizing output fluctuations with power generation based on renewable energy, the stabilization of power supply can be achieved.
[0003] As a device for storing electric energy in an electric energy storage system, for example, a secondary battery can be cited. The secondary battery used in the electric energy storage system needs to have a large capacity, and therefore, lithium-ion secondary batteries (LIBs) that have a high energy density per unit volume and mass and can be miniaturized have attracted much attention. At present, carbon materials are generally used as negative electrode materials for lithium-ion secondary batteries. As negative electrode materials other than carbon, metals such as Si, Sn, Ti and V, metal oxides containing the above metals and lithium, and mixed materials of carbon and the above metals are in the research stage.
[0004] Among carbon materials, if graphite materials are used as negative electrode materials, lithium-ion secondary batteries with high discharge capacity can be obtained. Therefore, they are widely used in lithium-ion secondary batteries for portable electronic devices. On the other hand, as ESS applications, non-graphitizable carbon materials with high discharge capacity and good cycle characteristics are suitable. In particular, unlike secondary batteries for hybrid vehicles, ESS applications strongly require charging capacity that can be charged at a large capacity at a low charging rate, high volume capacity for miniaturization, and life characteristics that can be repeatedly charged and discharged for a long time.
[0005] The structural characteristics of the difficult graphitized carbon used as the negative electrode material of the lithium ion secondary battery include: the graphite unit with a small crystallite diameter is crystallized in an unoriented manner, the graphite unit has pores, and the interlayer distance (c-axis length) of the stacking direction of the graphene in the graphite unit is long. Due to these structural characteristics, Li can be occluded not only between layers but also in pores. Therefore, it is known that compared with the theoretical capacity of 372mAh / g of graphite (pure graphite), the difficult graphitized carbon has a higher charge and discharge capacity. In addition, due to the long c-axis length, the volume change accompanying the insertion / extraction of Li is small, and the life characteristics (cycle characteristics) are also excellent.
[0006] As a non-graphitizable carbon, for example, Patent Document 1 discloses that a carbon material having a large lithium storage capacity can be obtained by setting an index related to the crystallite diameter in the c-axis direction obtained by X-ray diffraction and the interplanar spacing corresponding to the 002 reflection to a specific range.
[0007] Patent document 2 discloses a non-aqueous electrolyte secondary battery using a carbon material having a crystallite diameter in the c-axis direction, a lattice spacing corresponding to 002 reflection, and a crystallite diameter in the a-axis direction within a given range as determined by X-ray diffraction.
[0008] Prior art literature
[0009] Patent Literature
[0010] Patent Document 1: Japanese Patent Application Laid-Open No. 8-180868
[0011] Patent Document 2: Japanese Patent Application Laid-Open No. 10-21915 Summary of the invention
[0012] Problems to be solved by the invention
[0013] On the other hand, currently, the crystallite diameter of carbon materials is calculated using the Scherrer formula and the Gakushin method, that is, it is calculated only based on the half-width of the diffraction peak in the X-ray diffraction pattern, without taking into account the expansion of the half-width caused by the strain of the carbon material.
[0014] The present inventors have studied the structure and production method of non-graphitizable carbon with high discharge capacity. As a result, they found that it is difficult to obtain sufficient discharge capacity by simply controlling the crystallite diameter obtained by the existing method to a specific range, and improvement is needed.
[0015] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a non-graphitizable carbon, a mixed carbon powder, a negative electrode for a lithium ion secondary battery, and a lithium ion secondary battery capable of obtaining a high discharge capacity.
[0016] Solutions to the problem
[0017] The inventors have conducted intensive research to solve the above problems and have found that the above problems can be solved when the strain information of the carbon material is obtained by the Williamson-Hall method and the interplanar spacing corresponding to the 002 reflection is within a given range, thereby completing the present invention. That is, it has been found that the above problems can be solved by the following configuration.
[0018] [1] A non-graphitizable carbon having a strain ε of 0.081 to 0.120, wherein the strain ε is obtained by performing a Rietveld analysis on an X-ray diffraction pattern to obtain a profile and using the profile to obtain the profile by a Williamson-Hall method,
[0019] The interplanar spacing d002 corresponding to the 002 reflection obtained by performing Tewold analysis on the X-ray diffraction pattern was 0.360 to 0.370 nm.
[0020] [2] A negative electrode for a lithium ion secondary battery, comprising the non-graphitizable carbon described in [1].
[0021] [3] A lithium ion secondary battery comprising the negative electrode for a lithium ion secondary battery according to [2].
[0022] [4] A mixed carbon powder comprising the non-graphitizable carbon described in [1] and graphite, wherein:
[0023] The content of the non-graphitizable carbon is 1 to 20% by mass relative to the total mass of the mixed carbon powder.
[0024] The remainder is the graphite.
[0025] [5] A negative electrode for a lithium ion secondary battery, comprising the mixed carbon powder described in [4].
[0026] [6] A lithium ion secondary battery comprising the negative electrode for a lithium ion secondary battery according to [5].
[0027] Effects of the Invention
[0028] According to the present invention, it is possible to provide hardly graphitizable carbon capable of obtaining a high discharge capacity, a negative electrode for a lithium ion secondary battery, and a lithium ion secondary battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 It is a cross-sectional view showing a coin-type secondary battery for evaluation.
[0030] Reference numerals
[0031] 1: External cup
[0032] 2: Working electrode
[0033] 3: External can
[0034] 4: Counter electrode
[0035] 5: Partition
[0036] 6: Insulation pad
[0037] 7a: Current Collector
[0038] 7b: Current Collector DETAILED DESCRIPTION
[0039] Hereinafter, the present invention will be described in detail.
[0040] Although the description of the constituent elements described below may be based on representative embodiments of the present invention, the present invention is not limited to such embodiments.
[0041] The meanings of the various descriptions in this specification are shown below.
[0042] Hereinafter, an embodiment of the present invention will be described in detail. However, the embodiment described below is an example, and the present invention is not limited to the embodiment described below.
[0043] In addition, the numerical range expressed using "to" in this specification means a range including the numerical values described before and after "to" as the lower limit and the upper limit.
[0044] [Difficult to graphitize carbon]
[0045] For the difficult-to-graphitize carbon of the present invention, a profile is obtained by Rietveld analysis of the X-ray diffraction pattern, and the strain ε obtained using the above profile and the Williamson-Hall method is 0.081~0.120, and the crystal plane spacing d002 corresponding to the 002 reflection obtained by Rietveld analysis of the above X-ray diffraction pattern is 0.360~0.370nm.
[0046] The detailed conditions of the Tewold analysis and the Williamson-Hall method will be described in detail later.
[0047] The mechanism of obtaining high discharge capacity by controlling strain ε is not necessarily clear, but the inventors speculate as follows. That is, it can be considered that when the strain ε is 0.081 or more, defects such as vacancies are introduced into the layer structure, and Li can be absorbed in the defects such as vacancies to obtain high discharge capacity. On the other hand, if the strain ε exceeds 0.120, the amount of defects such as vacancies increases, the density of difficult graphitized carbon decreases, and the discharge capacity per unit volume decreases, so the strain ε is set to 0.120 or less.
[0048] The method for controlling the strain ε is not particularly limited. For example, by making the infusibility described later a multi-step process to make the oxidation degree inside the particles uniform, the strain ε can be controlled within a given range. In addition, there is a tendency that the lower the temperature at which the raw material of the non-graphitizable carbon is calcined, the larger the particle size of the non-graphitizable carbon is, and the larger the strain ε introduced by calcining.
[0049] As described above, the non-graphitizable carbon of the present invention has a lattice spacing d002 corresponding to the 002 reflection obtained by the Tewold analysis (hereinafter also simply referred to as “lattice spacing d002”) of 0.360 nm to 0.370 nm.
[0050] The mechanism of obtaining high discharge capacity by controlling interplanar spacing d002 is not necessarily clear, but the inventors speculate as follows. That is, it can be considered that when interplanar spacing d002 is more than 0.360nm, the embedding / de-embedding mouth of Li is large and Li can be easily embedded / de-embedded, and a large amount of interlayer Li occlusion sites can be effectively fully utilized to obtain high discharge capacity. In addition, when the interlayer distance of graphene is repeatedly changed with the embedding / de-embedding of Li, the crystalline structure is not easy to destroy, and good cycle characteristics can also be obtained. Interplanar spacing d002 is preferably more than 0.361nm. On the other hand, when interplanar spacing d002 exceeds 0.370nm, the density of difficult graphitizable carbon is reduced, and the discharge capacity per unit volume is reduced, therefore, interplanar spacing d002 is set to less than 0.370nm. Interplanar spacing d002 is preferably less than 0.366nm.
[0051] The method for controlling the interplanar spacing d002 is not particularly limited. For example, as the raw material of the non-graphitizable carbon, a raw material can be selected that can make the interplanar spacing d002 reach the range of the present invention by firing. For example, it can be selected from asphalts such as coal-based asphalt and petroleum-based asphalt; resins such as phenolic resin and furan resin; mixtures of asphalt and resin, etc. From the point of view that the interplanar spacing d002 can easily reach a given range, coal-based asphalt is particularly preferred.
[0052] From the viewpoint of suppressing the reaction with the electrolyte, the specific surface area (BET specific surface area) of the non-graphitizable carbon of the present invention measured by the BET method using nitrogen is preferably 10 m 2 / g or less, more preferably 1 to 6 m 2 / g.
[0053] The average particle size of the non-graphitizable carbon of the present invention is preferably 1 to 50 μm, more preferably 20 to 35 μm.
[0054] It should be noted that the above average particle size refers to the particle size (D 50 ).
[0055] The true density of the non-graphitizable carbon of the present invention is preferably 1.45 g / cm 3 More preferably, 1.47 g / cm 3 More preferably, 1.49 g / cm 3The true density was determined by a liquid phase replacement method using a pycnometer using butanol according to the method described in JIS R7222.
[0056] In addition, for the difficult graphitizable carbon of the present invention, assuming that the shape of the difficult graphitizable carbon is a dense sphere, the ratio of the above-mentioned BET specific surface area to the specific surface area calculated according to the above-mentioned average particle size and the above-mentioned true density is preferably 30.0 or less, more preferably 10.0 or less, and further preferably 5.0 or less. When the above-mentioned ratio is within the preferred range, the surface of the difficult graphitizable carbon is small and the reaction with the electrolyte can be suppressed.
[0057] [Rietveld analysis]
[0058] In the present invention, the Tewold analysis is performed according to the following steps.
[0059] First, an X-ray diffraction measurement of the non-graphitizable carbon is performed to obtain an X-ray diffraction pattern of the non-graphitizable carbon. The X-ray diffraction measurement is set to X-ray: CuKα line, scanning range (2θ): 3 to 90°, step: 0.02°, and an X-ray diffraction pattern is obtained. The scanning rate is adjusted so that the peak intensity of the 002 reflection falls between 1000 and 3000 counts.
[0060] The X-ray diffraction measuring apparatus used was Ultima IV manufactured by Rigaku Corporation, and a single light instrument was not used. It should be noted that for the sample for measuring the difficult graphitizable carbon, CeO2 (cerium dioxide manufactured by NIST) as an internal standard was mixed with the difficult graphitizable carbon using a mortar in such a manner that it accounted for 5% by mass of the total mass, and the obtained powder was filled into the tank.
[0061] Next, the obtained X-ray diffraction pattern was subjected to Tewold analysis under the following conditions. Tewold analysis was based on "The Reality of Powder X-ray Analysis (2nd Edition)" edited by Izumi Nakai and Fujio Izumi, published by Asakura Bookstore (2009). It should be noted that the peaks corresponding to the respective wavelengths of CuKα1 (0.1540593 nm) and CuKα2 (0.1544427 nm) were analyzed.
[0062] First, the atomic displacement parameters and selective orientation parameters are calculated under the following conditions.
[0063] Initial structure: Non-graphitizable carbon: ICSD No.: 76767 (P63 / mmc), Internal standard CeO2 (NIST): ICSD No.: 24887
[0064] Analysis software: RIETAN-FP (ver2.32)
[0065] Contour function: Non-smooth reflection: Tiger Valley segmentation, pseudo-Voigt function, Smooth reflection: Extended segmentation pseudo-Voigt function
[0066] Tewold analysis angle: 2θ: 3 to 90°
[0067] Here, the following parameters are optimized under the following conditions.
[0068] 1. Background parameters (8)
[0069] 2. Scale factor (1) × 2 phases
[0070] 3. Contour function: non-smooth reflection: Tiger Valley segmentation, pseudo-Voigt function, slow reflection: extended segmentation pseudo-Voigt function, contour parameters (11) × 2 phasors
[0071] 4. Lattice constants of non-graphitizable carbon: a-axis and c-axis (2), lattice constant of internal standard CeO2: a-axis (1)
[0072] 5. Atomic displacement parameters, difficult-to-graphitize carbon: 2b site, 2c site (2), internal standard CeO2: 4a site, 8c site (2)
[0073] 6. Selective orientation parameters, difficult to graphitize carbon: (001), (100), (101) (3), the selective orientation of CeO2 is not considered.
[0074] The initial values of the parameters were adjusted and the analysis was repeated until the analysis converged, Rwp (weighted reliability factor) was less than 7, and S (Goodness of fit indicator) was less than 2. The obtained atomic displacement parameters and selective orientation parameters were used for subsequent analysis.
[0075] Next, the lattice constants (a-axis and c-axis) of the hardly graphitizable carbon were calculated.
[0076] Initial structure: the optimized structure above
[0077] Profile function: pseudo-Voigt function of Thompson, Cox, Hastings (TCH)
[0078] Tewold analysis angle: 2θ: 3 to 90°
[0079] Here, the following parameters are optimized.
[0080] 1. Background parameters (8)
[0081] 2. Scale factor (1) × 2 phases
[0082] 3. Profile function: Thompson, Cox, Hastings (TCH) pseudo-Voigt function, profile parameters (7)
[0083] 4. Lattice constants of non-graphitizable carbon: a-axis, c-axis (2) Lattice constant of internal standard CeO2 a-axis (1)
[0084] The analysis is repeated while adjusting the initial values of the parameters, and the analysis is repeated until the analysis converges, Rwp becomes less than 7, and S becomes less than 2. The value obtained by dividing the obtained c-axis lattice constant by 2 is taken as the interplanar spacing d002.
[0085] [Williamson-Hall method]
[0086] In the present invention, analysis based on the Williamson-Hall method is performed in the following steps.
[0087] For the peaks corresponding to the wavelengths of CuKα1 and CuKα2 in the profile of the X-ray diffraction pattern obtained by the Tewold analysis, the crystallite diameter D and the strain ε were calculated according to the following formula based on the half-value width β [rad] of each diffraction angle θ [rad]. It should be noted that λ is the wavelength of the X-ray, and the wavelength of CuKα1 is 0.1540593nm, and the wavelength of CuKα2 is 0.1544427nm.
[0088] βcosθ / λ=2εsinθ / λ+1 / D
[0089] Here, the vertical axis is set to βcosθ / λ and the horizontal axis is set to 2sinθ / λ, and the strain ε can be obtained from the slope obtained by fitting using the least square method. The above plot is also called a Williamson-Hall plot.
[0090] From the point of view of obtaining a high discharge capacity, the difficult graphitizable carbon of the present invention can be suitably used as a negative electrode active material for a negative electrode for a lithium ion secondary battery. The negative electrode for a lithium ion secondary battery using the difficult graphitizable carbon of the present invention may contain, in addition to the difficult graphitizable carbon of the present invention, components and members commonly used in negative electrodes for lithium ion secondary batteries.
[0091] [Method for producing non-graphitizable carbon]
[0092] Hereinafter, an example of a method for producing the non-graphitizable carbon of the present invention will be described. It should be noted that the method for producing the non-graphitizable carbon of the present invention is not limited to the following example.
[0093] Examples of a method for producing non-graphitizable carbon include a method of cross-linking a raw material of non-graphitizable carbon, rendering the resulting cross-linked product infusible, pulverizing the resulting infusible product, and calcining the resulting pulverized product.
[0094] Each process is described below.
[0095] [Cross-linking treatment]
[0096] First, a raw material of non-graphitizable carbon (hereinafter, also simply referred to as "raw material") is subjected to a cross-linking treatment to obtain a cross-linked product.
[0097] Here, the raw materials used in the examples of the manufacturing method are not particularly limited, and currently known raw materials can be used. As raw materials, for example, asphalts such as coal-based asphalt and petroleum-based asphalt; resins such as phenolic resin and furan resin; mixtures of asphalt and resin, etc. Among them, from the viewpoint of economy, asphalts such as coal-based asphalt and petroleum-based asphalt are preferred.
[0098] As a method for cross-linking the above-mentioned raw materials, for example, there can be cited a method based on air blowing reaction; a dry method based on an oxidizing gas (air, oxygen, ozone); a wet method using an aqueous solution of nitric acid, sulfuric acid, hypochlorous acid, a mixed acid, etc., among which the method based on air blowing reaction is preferred.
[0099] The air blowing reaction is a reaction in which the softening point is raised by heating the above raw materials and blowing an oxidizing gas (e.g., air, oxygen, ozone, or a mixture thereof). According to the air blowing reaction, a cross-linked product (e.g., air-blown asphalt) having a high softening point of, for example, 200° C. or more can be obtained.
[0100] It should be noted that, according to Japanese Patent Application Laid-Open No. 9-153359, it is known that the air blowing reaction is a reaction in a liquid phase state, and compared with the cross-linking treatment in a solid phase state, oxygen atoms are basically not incorporated into the carbon material.
[0101] In the blowing reaction, an oxidative dehydration reaction is carried out as the main reaction, and polymerization is carried out through biphenyl-type cross-linking bonds. Then, through subsequent infusibility and sintering (described later), the cross-linked portion has a three-dimensional structure with no dominant orientation, and a large amount of pores for absorbing and releasing lithium can be obtained.
[0102] The conditions of the air blowing reaction are not particularly limited. From the perspective of suppressing the generation of an intermediate phase when the temperature is too high and increasing the reaction rate, the reaction temperature is preferably 280 to 420°C, and more preferably 320 to 380°C. In addition, the blowing amount of the oxidizing gas is preferably 0.5 to 15 L / min per 1000 g of asphalt in terms of compressed air, and more preferably 1.0 to 10 L / min. The reaction pressure may be any of normal pressure, reduced pressure, and pressurized pressure, and is not particularly limited.
[0103] The softening point of the cross-linked product such as air-blown pitch obtained by such a cross-linking treatment is preferably 200 to 400°C, more preferably 250 to 350°C, from the perspective of ease of subsequent infusibility treatment.
[0104] The obtained cross-linked product may be coarsely pulverized using an atomizer or the like before being subjected to the infusibility treatment.
[0105] [Infusible treatment]
[0106] Next, the cross-linked product such as the air-blown asphalt is subjected to an infusible treatment to obtain an infusible product (e.g., infusible asphalt). The infusible treatment is a cross-linking treatment (oxidation treatment) performed in a solid phase, whereby oxygen is incorporated into the structure of the cross-linked product, and further cross-linking is performed to make it difficult to melt at high temperatures.
[0107] There are no particular limitations on the method of infusibility treatment, and examples thereof include a dry method using an oxidizing gas (air, oxygen); a wet method using an aqueous solution of nitric acid, sulfuric acid, hypochlorous acid, a mixed acid, etc. Among these, a dry method using an oxidizing gas is preferred.
[0108] The treatment temperature for the infusibility treatment is preferably selected to be below the softening point of the crosslinked product. In order to further prevent fusion, the heating rate in batch treatment is preferably 5 to 100°C / hour, more preferably 10 to 50°C / hour.
[0109] From the viewpoint of making the degree of oxidation inside the particles uniform and homogenous and obtaining stable properties of the non-graphitizable carbon, the number of times of the infusibility treatment is preferably divided into two or more times.
[0110] As a method of dividing the infusibility treatment into two or more times, specifically, there is a method of increasing the temperature of the infusibility treatment stepwise.
[0111] For example, the following method can be cited: the temperature is raised to the first set temperature at the above-mentioned preferred temperature rate, and an infusibility treatment is performed at the first set temperature for a given time, and then the temperature is raised to the second set temperature at the above-mentioned preferred temperature rate, and an infusibility treatment is performed at the second set temperature for a given time.
[0112] The first set temperature may be appropriately set according to the softening point of the cross-linked product, and is preferably 100 to 400° C., more preferably 150 to 300° C. The treatment time at the first set temperature is preferably 0.5 to 3 hours, more preferably 0.5 to 2 hours.
[0113] The second set temperature may be appropriately set according to the softening point of the crosslinked product after treatment at the first set temperature, and is preferably 100 to 450° C., more preferably 150 to 350° C. The treatment time at the second set temperature is preferably 1 to 15 hours, more preferably 2 to 10 hours.
[0114] It should be noted that the second set temperature is preferably higher than the first set temperature. The second set temperature is preferably 20 to 150°C higher than the first set temperature, and more preferably 30 to 100°C higher.
[0115] The other treatment conditions in the infusibility treatment are not particularly limited. For example, the blowing amount of the oxidizing gas is preferably 1.0 to 20 L / min, more preferably 2.0 to 10 L / min per 1000 g of compressed air. The reaction pressure may be any of normal pressure, reduced pressure, and pressurized pressure, and is not particularly limited.
[0116] The oxygen content of the infusible product obtained by the infusible treatment is preferably 3 to 20% by mass, more preferably 5 to 15% by mass, from the viewpoint of preventing fusion during firing.
[0117] [Crushing treatment]
[0118] Next, the infusible product such as infusible pitch is pulverized to adjust the particle size. At this time, the average particle size of the infusible product after pulverization is preferably 1 to 50 μm, more preferably 20 to 35 μm.
[0119] It should be noted that the average particle size here refers to the particle size (D 50 ).
[0120] The pulverizer used for the pulverization treatment is not particularly limited, and a conventionally known method can be used, and examples thereof include a jet mill, a pin mill, a ball mill, a hammer mill, a roll mill, and a vibration mill.
[0121] When using these pulverizers, the pulverization conditions are set so that the average particle size of the infusible product after the pulverization process falls within the above-mentioned range.
[0122] [Firing treatment]
[0123] Next, the infusible treated product such as the infusible pitch subjected to the pulverization treatment is fired in a reduced pressure or inert gas atmosphere such as nitrogen to obtain a non-graphitizable carbon material. The reaching temperature (firing temperature) during the firing is preferably 600 to 880°C, more preferably 650 to 850°C, and further preferably 680 to 820°C. At this time, the heating rate is preferably 50 to 150°C / hour, and more preferably 80 to 120°C / hour.
[0124] [Mixed Toner]
[0125] The hardly graphitizable carbon of the present invention can be mixed with graphite to prepare a mixed carbon powder for use.
[0126] Thus, even if the charge and discharge conditions are set to low temperature and high rate while maintaining a high discharge capacity, more excellent cycle characteristics can be obtained.
[0127] The content of the hardly graphitizable carbon is, for example, 1 mass % or more, and preferably 2 mass % or more, based on the total mass of the mixed carbon powder, in order to obtain more excellent cycle characteristics.
[0128] On the other hand, the content of the hardly graphitizable carbon is, for example, 20 mass % or less, and preferably 15 mass % or less, based on the total mass of the mixed carbon powder in order to obtain a higher average operating voltage.
[0129] The content of graphite in the mixed carbon powder is preferably the remainder of the non-graphitizable carbon. Specifically, the content of graphite is preferably 80 to 99% by mass, more preferably 85 to 98% by mass, relative to the total mass of the mixed carbon powder.
[0130] The graphite contained in the mixed carbon powder is not particularly limited, and may be natural graphite or artificial graphite. In addition, the graphite contained in the mixed carbon powder may also contain natural graphite and artificial graphite. The raw materials used in the manufacture of artificial graphite are not particularly limited, and petroleum coke and coal coke may be cited.
[0131] The interplanar spacing d002 of the graphite is preferably 0.359 nm or less, more preferably 0.350 nm or less, and most preferably 0.340 nm or less.
[0132] [Lithium-ion secondary battery]
[0133] Hereinafter, a lithium ion secondary battery using the hardly graphitizable carbon of the present invention in a negative electrode for a lithium ion secondary battery (hereinafter also referred to as “the lithium ion secondary battery of the present invention”) will be described.
[0134] Lithium-ion secondary batteries usually have a negative electrode, a positive electrode, and a non-aqueous electrolyte as the main battery components. The positive electrode and the negative electrode are respectively formed by substances (such as layered compounds), compounds, or clusters that can absorb Li. During the charge and discharge process, lithium ions are absorbed and released from the positive electrode and the negative electrode. More specifically, it is a battery mechanism in which lithium ions are doped into the negative electrode during charging, and Li is dedoped from the negative electrode during discharge.
[0135] The lithium ion secondary battery of the present invention is not particularly limited except that the non-graphitizable carbon of the present invention is used as a negative electrode material, and other battery components are based on the components of a general lithium ion secondary battery.
[0136] It should be noted that, below, the case where the hardly graphitizable carbon of the present invention is used for a negative electrode of a lithium ion secondary battery is described, and the configuration when the mixed carbon powder is used is the same as that when the hardly graphitizable carbon of the present invention is used.
[0137] [negative electrode]
[0138] The negative electrode made of the difficult graphitizable carbon of the present invention is not particularly limited and can be used as a common negative electrode. The negative electrode may contain a binder together with the difficult graphitizable carbon of the present invention. As a binder, it is preferred to use a binder that has chemical stability and electrochemical stability relative to the electrolyte, and it is usually preferably set to about 1 to 20% by mass in the total amount of the negative electrode mixture. As a binder, polyvinylidene fluoride, carboxymethyl cellulose (CMC), styrene butadiene rubber (SBR) and the like can be used. In addition, as an active material, a carbon material other than the difficult graphitizable carbon of the present invention (such as a graphite material) may be included. In addition, as a conductive agent, for example, carbon black, carbon fiber, etc. may be included.
[0139] The negative electrode mixture coating in a paste form is prepared by mixing the difficult graphitizable carbon material of the present invention with a binder, and the negative electrode mixture coating is usually applied to one or both sides of the collector to form a negative electrode mixture layer for use. In this case, a common solvent can be used to prepare the negative electrode mixture coating. The shape of the collector used for the negative electrode is not particularly limited, and examples thereof include: foil; mesh, porous metal and other meshes. Examples of the collector include copper, stainless steel, nickel and the like.
[0140] [positive electrode]
[0141] As the positive electrode material (positive electrode active material), it is preferred to select a material that can be doped / dedoped with a sufficient amount of lithium ions. Examples of such positive electrode active materials include transition metal oxides, transition metal chalcogenides, vanadium oxides, and lithium-containing compounds thereof, and compounds of the general formula M X 6S 8-Y(wherein, X is a value in the range of 0≤X≤4, Y is a value in the range of 0≤Y≤1, and M represents a metal such as a transition metal) represented by a Chevreul phase compound, lithium iron phosphate, activated carbon, and activated carbon fiber. The positive electrode active material can be used alone or in combination of two or more. In addition, carbonates such as lithium carbonate can also be added to the positive electrode.
[0142] The lithium-containing transition metal oxide is a composite oxide of lithium and a transition metal, or may be an oxide formed by solid solution of lithium and two or more transition metals. Specifically, the lithium-containing transition metal oxide is LiM(1) 1-P M(2) P O2 (wherein P is a value in the range of 0≤P≤1, and M(1) and M(2) are composed of at least one transition metal element), or LiM(1) 2-Q M(2) Q O4 (wherein Q is a value in the range of 0≤Q≤1, and M(1) and M(2) are composed of at least one transition metal element). Here, the transition metal element represented by M includes Co, Ni, Mn, Cr, Ti, V, Fe, Zn, Al, In and Sn, and is preferably Co, Fe, Mn, Ti, Cr, V or Al.
[0143] Such lithium-containing transition metal oxides can be obtained by, for example, using Li and oxides or salts of transition metals as starting materials, mixing these starting materials according to the composition, and calcining them in an oxygen atmosphere at a temperature range of 600 to 1000° C. It should be noted that the starting materials are not limited to oxides or salts, and can also be synthesized from hydroxides and the like.
[0144] As a method for forming a positive electrode using such a positive electrode material, for example, a method for forming a positive electrode mixture layer by applying a paste of a positive electrode mixture coating formed by a positive electrode material, a binder and a conductive agent to one or both sides of a collector can be cited. As a binder, the binders exemplified in the negative electrode can be used. As a conductive agent, for example, particulate carbon materials, fibrous carbon materials, graphite, carbon black, VGCF (vapor grown carbon fiber) can be used. The shape of the collector is not particularly limited, and the same shape as the negative electrode can be used. As the material of the collector, aluminum, nickel, stainless steel foil, etc. can usually be used.
[0145] When forming the above-mentioned negative electrode and positive electrode, various additives such as conventionally known conductive agents and binders may be appropriately used.
[0146] [Electrolytes]
[0147] The electrolyte is not particularly limited as long as lithium ions can move, and may be a liquid non-aqueous electrolyte, a polymer electrolyte such as a gel electrolyte, or a solid electrolyte such as an oxide or a sulfide.
[0148] For example, the liquid non-aqueous electrolyte solution includes a general non-aqueous electrolyte containing a lithium salt such as LiPF6 and LiBF4 as an electrolyte salt.
[0149] When a liquid nonaqueous electrolyte is used, an aprotic organic solvent such as ethylene carbonate, propylene carbonate, or dimethyl carbonate can be used as the nonaqueous solvent.
[0150] In the case of being set as a polymer electrolyte, it includes a matrix polymer after being gelled with a plasticizer (non-aqueous electrolyte). As the matrix polymer, ether polymers such as polyethylene oxide and its crosslinked bodies, polymethacrylates, polyacrylates, polyvinylidene fluoride, fluorine-based polymers such as vinylidene fluoride-hexafluoropropylene copolymers, etc. can be used alone or in combination, wherein, from the viewpoint of redox stability, etc., fluorine-based polymers are preferably used.
[0151] As the electrolyte salt and the non-aqueous solvent constituting the plasticizer (non-aqueous electrolyte solution) contained in the polymer electrolyte, those that can be used for liquid electrolyte solutions can be used.
[0152] In the lithium ion secondary battery of the present invention, a separator such as a microporous body of polypropylene or polyethylene or a layer structure of these, or a nonwoven fabric is generally used.
[0153] Alternatively, a gel electrolyte may be used. In this case, for example, a negative electrode containing the hardly graphitizable carbon of the present invention, a gel electrolyte, and a positive electrode are sequentially stacked and housed in a battery exterior material.
[0154] The structure of the lithium ion secondary battery of the present invention is arbitrary, and its shape and form are not particularly limited. The shape of the lithium ion secondary battery can be arbitrarily selected from, for example, a cylindrical shape, a square shape, a sheet shape, and a coin shape.
[0155] Example
[0156] Hereinafter, the present invention will be described in more detail based on examples.
[0157] The materials, amounts, ratios, treatment contents and treatment procedures shown in the following examples may be appropriately changed without departing from the gist of the present invention. Therefore, the scope of the present invention should not be interpreted as being limited to the following examples.
[0158] [Manufacturing of carbon materials]
[0159] The carbon materials used in Examples and Comparative Examples were produced according to the following procedures.
[0160] [Example 1]
[0161] 1000 g of coal-based QI-free (insoluble impurities) asphalt (QI: 0.1-0.5 mass %, softening point: 82.5° C.) was placed in an autoclave equipped with an anchor-type stirring device and heated to 350° C. under a nitrogen stream. Then, compressed air was blown into the asphalt while flowing at 5 L / min and heated at 320° C. for 2 hours, thereby performing a crosslinking treatment based on an air blowing reaction. Then, the mixture was cooled to room temperature and the contents (air-blown asphalt) were taken out.
[0162] Next, the taken out air-blown asphalt was coarsely crushed with an atomizer, put into a rotary furnace, and heated at 20°C / hour while circulating compressed air at 5 L / min, and kept at 200°C for 1 hour. Then, the temperature was raised to 250°C again and kept for 5 hours to perform an infusibility treatment, thereby obtaining infusible asphalt.
[0163] The obtained infusible pitch was pulverized using a jet mill (FS-4, manufactured by Seishin Enterprise) under conditions where the average particle size of the pulverized product was 3 to 5 μm. 100 g of the infusible pitch after pulverization was placed in a graphite covered container, heated to a calcination temperature of 700°C at a heating rate of 100°C / hour under a nitrogen flow, and calcined at 700°C for 2 hours to obtain carbon powder (difficult to graphitize carbon).
[0164] [Examples 2 and 3]
[0165] In Examples 2 and 3, carbon powder (non-graphitizable carbon) was obtained in the same manner as in Example 1 except that the sintering temperature was changed to the temperature shown in Table 1 below.
[0166] [Comparative Example 1]
[0167] 1000 g of coal-based QI-free asphalt (QI: 0.1-0.5 mass %, softening point: 82.5° C.) was placed in an autoclave equipped with an anchor-type stirring device and heated to 320° C. under a nitrogen stream. Then, compressed air was blown into the asphalt while flowing at 2 L / min, and heated at 320° C. for 2 hours, thereby implementing a crosslinking treatment based on an air blowing reaction. Then, the mixture was cooled to room temperature and the contents (air-blown asphalt) were taken out.
[0168] Next, the air-blown asphalt was coarsely crushed with an atomizer, placed in a rotary furnace, and heated at 20°C / hour while circulating compressed air at 2 L / min, and then kept at 200°C for 1 hour. Then, the temperature was raised to 250°C again and kept for 3 hours to perform an infusibility treatment, thereby obtaining infusible asphalt.
[0169] 100 g of the obtained infusible asphalt was placed in a graphite container with a lid, heated to 900°C at a heating rate of 100°C / hour under a nitrogen flow, calcined at 900°C for 2 hours, and then pulverized under the same conditions as in Example 1 to obtain carbon powder.
[0170] [Comparative Example 2]
[0171] A carbon powder was obtained under the same conditions as in Comparative Example 1 except that the calcination temperature was 1100° C. and ethylene bottom oil was used as a raw material.
[0172] [Comparative Example 3]
[0173] A carbon powder was obtained under the same conditions as in Comparative Example 1 except that the sintering temperature was 1100° C. and the infusibility treatment was not performed.
[0174] [Comparative Examples 4 and 5]
[0175] Carbon powder was obtained under the same conditions as in Comparative Example 1 except that the sintering temperatures were 1200°C and 1600°C.
[0176] [Comparative Example 6]
[0177] The carbide of the mesophase carbon spheres obtained by calcining the mesophase spheres at 500° C. was pulverized using a jet mill to reduce the average particle size (D 50 ) was 3 μm, and then graphitized at 3000°C to obtain carbon powder.
[0178] [Measurement and evaluation]
[0179] [Measurement by X-ray diffraction]
[0180] For the carbon material obtained in each example and each comparative example, an X-ray diffraction pattern was obtained by the above-mentioned method, and the above-mentioned analysis was performed to obtain the strain ε and the interplanar spacing d002.
[0181] [Measurement of discharge capacity]
[0182] According to the following steps, a coin-type secondary battery for evaluation was prepared using the carbon materials obtained in each example and each comparative example as a negative electrode material (refer to Figure 1), and the discharge capacity was evaluated.
[0183] (Preparation of negative electrode mixture paste)
[0184] First, the obtained carbon powder was used as the negative electrode material to prepare the negative electrode mixture paste. Specifically, carbon powder (95 parts by mass) and a 12% N-methylpyrrolidone solution of polyvinylidene fluoride (PVDF) (5 parts by mass in terms of solid content) were placed in a planetary mixer, stirred at 100 rpm for 15 minutes, and N-methylpyrrolidone was further added to adjust the solid content ratio to 60%, and stirring was continued for 15 minutes to prepare the negative electrode mixture paste.
[0185] (Production of negative electrode)
[0186] The prepared negative electrode mixture paste was applied to the copper foil in a uniform thickness, and then placed in a blower dryer to volatilize the solvent at 100°C to form a negative electrode mixture layer. Next, the negative electrode mixture layer was pressurized using a roller press and further punched into a circle with a diameter of 15.5 mm, thereby producing a negative electrode having a negative electrode mixture layer that was closely attached to the collector formed by the copper foil. It should be noted that before evaluation, drying was performed at 100°C in a vacuum for more than 8 hours.
[0187] (Preparation of Electrolyte)
[0188] In a mixed solvent of ethylene carbonate (33% by volume) and ethyl methyl carbonate (67% by volume), LiPF6 was added at a concentration of 1 mol / dm 3 The concentration of was dissolved to prepare a non-aqueous electrolyte.
[0189] (Evaluation of battery manufacturing)
[0190] Next, using the prepared negative electrode, Figure 1 The coin-type secondary battery for evaluation (also simply referred to as "evaluation battery") is shown. Figure 1 is a cross-sectional view showing a coin-type secondary battery for evaluation.
[0191] First, a lithium metal foil was pressed against a nickel mesh and punched out into a circle with a diameter of 15.5 mm, thereby producing a disk-shaped counter electrode 4 made of lithium foil in close contact with a current collector 7 a made of the nickel mesh.
[0192] Next, the separator 5 impregnated with the electrolyte solution is sandwiched between the working electrode (negative electrode) 2 tightly attached to the collector 7b and the counter electrode 4 tightly attached to the collector 7a, and then the working electrode 2 is contained in the outer cup 1, the counter electrode 4 is contained in the outer can 3, the outer cup 1 and the outer can 3 are joined, and the edges of the outer cup 1 and the outer can 3 are riveted and sealed with an insulating pad 6, thereby producing an evaluation battery.
[0193] In the manufactured evaluation battery, the edges of the outer cup 1 and the outer can 3 are riveted with an insulating pad 6 sandwiched therebetween to form a sealed structure. Figure 1 As shown, the current collector 7a, the counter electrode 4, the separator 5, the working electrode (negative electrode) 2 and the current collector 7b are stacked in this order from the inner surface of the outer can 3 toward the inner surface of the outer cup 1.
[0194] (Charge and discharge test)
[0195] The prepared evaluation battery was subjected to the following charge and discharge test at 25° C. In this test, the process of doping carbon powder with lithium ions is called “charge”, and the process of dedoping carbon powder is called “discharge”.
[0196] First, a constant current charge is performed at a current value of 0.39mA until the circuit voltage reaches 0mV, and then a constant voltage charge is switched to the moment when the circuit voltage reaches 0mV, and then the charge is continued until the current value reaches 20μA. The first charge capacity (unit: mAh / g) is calculated based on the amount of power supplied during this period. Then, stop for 120 minutes. Next, a constant current discharge is performed at a current value of 0.39mA until the circuit voltage reaches 1.5V, and then a constant voltage discharge is switched to the moment when the circuit voltage reaches 1.5V, and then the discharge is continued until the current value reaches 20μA. The first discharge capacity (unit: mAh / g) is calculated based on the amount of power supplied during this period.
[0197] [result]
[0198] Table 1 shows the results of measurement and evaluation of each Example and each Comparative Example.
[0199] Table 1
[0200]
[0201] The results in Table 1 confirm that, compared with the comparative examples in which at least one of the strain ε and the interplanar spacing d002 is not within the given range, the embodiments in which the strain ε is within the given range and the interplanar spacing d002 is within the given range can obtain a high discharge capacity.
[0202] [Evaluation of mixed toner]
[0203] Evaluation was performed on the case where a mixed carbon powder obtained by mixing the above-mentioned carbon powder (non-graphitizable carbon) and graphite was used as a carbon material for a negative electrode.
[0204] The carbon material (mixed carbon powder) used in the examples was produced according to the following procedure.
[0205] [Examples 4 to 8]
[0206] The carbon powder (hard-graphitizable carbon) obtained in Example 3 and needle coke-based graphite having an average particle size of 10 μm (interplanar spacing d002 of 0.336 nm) were mixed in the mixing ratio shown in Table 2 below to obtain mixed carbon powder.
[0207] [Measurement and evaluation]
[0208] [Charge and discharge test]
[0209] According to the following procedure, a secondary battery for evaluation was prepared using the mixed carbon powder obtained in each example as a negative electrode material, and a charge and discharge test was performed.
[0210] (Negative electrode and electrolyte)
[0211] A negative electrode mixture was obtained in the same manner as in the above steps, and a negative electrode and an electrolyte were prepared. The negative electrode was punched out into a size of 32 mm×52 mm and molded.
[0212] (positive electrode)
[0213] Chemical formula LiNi 0.3 Co 0.3 Mn 0.3 A layered rock salt structure lithium cobalt composite oxide of O3 was used as the positive electrode active material. 5 parts by mass of acetylene black as a conductive agent and 5 parts by mass of PVDF as a binding material were mixed with 90 parts by mass of the composite oxide, and an appropriate amount of N-methyl-2-pyrrolidone was added and fully kneaded to obtain a positive electrode paste.
[0214] The positive electrode paste was applied to one side of a 50 μm thick aluminum foil current collector using a doctor blade, dried, and then compressed by pressing to form a 50 μm thick positive electrode active material layer on the aluminum foil current collector. The current collector with the positive electrode active material formed thereon was punched out into a 30 mm x 50 mm rectangle.
[0215] (Evaluation of battery manufacturing)
[0216] The positive electrode and negative electrode obtained by the above steps were placed opposite to each other with a separator interposed therebetween, inserted into an Al laminate, injected with an electrolyte, and then vacuum-sealed to prepare an evaluation battery.
[0217] (Charge and discharge test)
[0218] The following charge and discharge tests were performed on the prepared evaluation cells. In this test, the process of doping carbon powder with lithium ions is referred to as "charging", and the process of dedoping carbon powder is referred to as "discharging".
[0219] First, at 25°C, CC (Constant Current) charging was performed at a charge rate of 0.05C to 3.6V, and further CCCV (Constant Current-Constant Voltage) charging was performed at 0.2C to 4.2V. The lower limit of the current was set to 0.05C. Next, CC discharge was performed at a discharge rate of 0.2C to 2.7V at 25°C. Under the above discharge conditions, the average value of the voltage during discharge was taken as the average voltage.
[0220] Next, the charge and discharge conditions were changed to seven conditions in the following order, and the charge and discharge were repeated for 10 cycles under each condition. Both the charge and discharge were set to CC mode, and the charge was performed until the voltage reached 4.2V, and the discharge was performed until the voltage reached 2.7V.
[0221] Condition 1: 25°C, charge / discharge rate 0.20C
[0222] Condition 2: 25°C, charge / discharge rate 0.50C
[0223] Condition 3: 25°C, charge / discharge rate 1.00C
[0224] Condition 4: 10°C, charge / discharge rate 0.75C
[0225] Condition 5: 10°C, charge / discharge rate 1.00C
[0226] Condition 6: 0°C, charge / discharge rate 0.50C
[0227] Condition 7: 0°C, charge / discharge rate 0.75C
[0228] The coulombic efficiency and capacity retention ratio were determined under each condition, and the cycle characteristics under each condition were evaluated based on the coulombic efficiency and capacity retention ratio. The results are shown in Table 2 below.
[0229] A: The coulombic efficiency of the second cycle is more than 99%, and the capacity retention rate is more than 94%.
[0230] B: If the above requirement A is not met
[0231] It should be noted that the coulombic efficiency refers to the value obtained by (discharge capacity at the second cycle / charge capacity at the second cycle)×100 (unit: %), and the capacity retention rate refers to the value obtained by (discharge capacity at the second cycle / discharge capacity at the tenth cycle)×100 (unit: %).
[0232] [result]
[0233] Table 2 shows the evaluation results when the mixed toner was used.
[0234]
[0235] As shown in Table 2, Examples 4 to 8 using the carbon powder (difficult-graphitizable carbon) of Example 3 were compared. Compared with Example 7 in which the content of difficult-graphitizable carbon was 1 mass %, Examples 4 to 6 and 8 in which the content of difficult-graphitizable carbon was more than 2 mass % had good cycle characteristics.
[0236] In addition, compared with Example 8 in which the content of the non-graphitizable carbon was 17 mass %, Examples 4 to 7 in which the content of the non-graphitizable carbon was 15 mass % or less obtained a high average voltage.
[0237] Industrial Applicability
[0238] The hardly graphitizable carbon of the present invention is suitable as a negative electrode material for lithium ion secondary batteries, and can be expected to be used in various industrial fields.
Claims
1. A non-graphitizable carbon having a strain ε of 0.081 to 0.120, wherein the strain ε is obtained by performing the following Tewold analysis on an X-ray diffraction pattern to obtain a profile and using the profile to obtain the profile by the following Williamson-Hall method, The interplanar spacing d002 corresponding to the 002 reflection obtained by performing Tewold analysis on the X-ray diffraction pattern is 0.360 to 0.370 nm. The raw material of the non-graphitizable carbon is coal-based pitch. A. Tewolde Analysis The X-ray diffraction measurement of the non-graphitizable carbon was performed, and the obtained X-ray diffraction pattern was subjected to Tewold analysis under the following conditions: The conditions for calculating atomic displacement parameters and selected orientation parameters are: Initial structure: non-graphitizable carbon: ICSD No.: 76767P63 / mmc, internal standard CeO2 from NIST: ICSD No.: 24887; Analysis software: RIETAN-FP ver2.32; Contour function: non-soft reflection: Tiger Valley segmentation, pseudo-Voigt function, soft reflection: extended segmentation pseudo-Voigt function; Tewold analysis angle: 2θ: 3 to 90°, in, The following parameters were optimized according to the following conditions:
1. 8 background parameters; 2. Scale factor 1 × 2 phasor; 3. Contour function: non-soft reflection: Tiger Valley segmentation, pseudo-Voigt function, soft reflection: extended segmentation pseudo-Voigt function, contour parameters 11 × 2 phasors; 4. The lattice constants of non-graphitizable carbon are two axes, a and c, and the lattice constant of internal standard CeO2 is one axis; 5. Atomic displacement parameters, difficult-to-graphitize carbon: 2b site, 2 2c sites, internal standard CeO2: 4a site, 2 8c sites; 6. Selective orientation parameters, difficult graphitizable carbon: (001), (100), (101), 3, ignoring the selective orientation of CeO2, Adjust the initial values of the parameters and repeat the analysis until the analysis converges, the weighted reliability factor Rwp is less than 7, and the fit index S is less than 2. The obtained atomic displacement parameters and selected orientation parameters are used for subsequent analysis. The conditions for calculating the lattice constants of the a-axis and c-axis of the non-graphitizable carbon are: Initial structure: the optimized structure above; Profile function: Thompson-Cox-Hastings, also known as TCH’s pseudo-Voigt function; Tewold analysis angle: 2θ: 3 to 90°, Among them, the following parameters are optimized:
1. 8 background parameters; 2. Scale factor 1 × 2 phasor; 3. Profile function: Thompson-Cox-Hastings, also known as TCH's pseudo-Voigt function, with 7 profile parameters; 4. Lattice constants of non-graphitizable carbon: 2 axes, a and c. The lattice constant of the internal standard CeO2 is 1 axis, Adjust the initial values of the parameters and repeat the analysis until the analysis converges, Rwp is less than 7, S is less than 2, and the value obtained by dividing the obtained c-axis lattice constant by 2 is taken as the interplanar spacing d002. B. Williamson-Hall method For the peaks corresponding to the respective wavelengths of CuKα1 and CuKα2 in the profile of the X-ray diffraction pattern obtained by the Tewold analysis, the crystallite diameter D and the strain ε are calculated according to the following formula based on the half-value width β of each diffraction angle θ, where the unit of the diffraction angle θ and the half-value width β is rad: βcosθ / λ=2εsinθ / λ+1 / D λ is the wavelength of X-rays. The wavelength of CuKα1 is 0.1540593nm, and the wavelength of CuKα2 is 0.1544427nm. Here, the plot was performed with βcosθ / λ on the vertical axis and 2sinθ / λ on the horizontal axis, and the strain ε was obtained from the slope obtained by fitting using the least square method.
2. A negative electrode for a lithium ion secondary battery, comprising the non-graphitizable carbon according to claim 1. 3 . A lithium ion secondary battery comprising the negative electrode for a lithium ion secondary battery according to claim 2 .
4. A mixed carbon powder comprising the non-graphitizable carbon according to claim 1 and graphite, wherein: The content of the non-graphitizable carbon is 1 to 20% by mass relative to the total mass of the mixed carbon powder. The remainder is the graphite. 5 . A negative electrode for a lithium ion secondary battery, comprising the mixed carbon powder according to claim 4 . 6 . A lithium ion secondary battery comprising the negative electrode for a lithium ion secondary battery according to claim 5 .
Citation Information
Patent Citations
Carbon material for lithium secondary battery negative electrode, its manufacture, carbon electrode and nonaqueous electrolytic lithium secondary battery
JP1996180868A
Manufacture of lithium secondary battery negative electrode material and its negative electrode material
JP1997153359A
Nonaqueous electrolyte secondary battery
JP1998021915A
Cathode active material, cathode electrode and non-aqueous secondary battery
CN104966827A
Negative electrode active material for lithium-ion secondary cell
CN105900269A
